SYNCHRONIC APPROACH IN LEXICAL-SEMANTIC ANALYSIS OF ECONOMIC TERMS IN THE BASIS OF THE ENGLISH AND UZBEK LANGUAGES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article deals with the field of terminology in Uzbek linguistics, namely, formation of economic terms that actively used in economic activities, their lexical-semantic (integral and differential) relations, in particular, in the phenomena of synonymy and polysemy.